Current Advances in Meerwein-type Radical Alkene Functionalizations - Diesendorf, Nina; Heinrich, Markus (Synthesis (Germany), 2022)
Alkene functionalizations via Meerwein arylations are becoming increasingly attractive, especially since a variety of mild and sustainable methods for aryl radical generation are available today. This entails a broad spectrum of substrates and radical scavengers, as well as convenient synthetic routes to relevant precursors for further transformations. The present review focuses on recent advances in Meerweintype alkene functionalizations and gives insights into the key mechanistic details of the respective reactions. 1 Introduction 2 Hydroarylation and Carboarylation 3 Carboamination, Carbooxygenation, and Carbothiolation 4 Carbohalogenation 5 Conclusion and Outlook
CRIS-Team Scopus Importer:2022-03-18
Keywords: Meerwein arylation; olefins; photocatalysis; radical chemistry; radical-polar crossover